Implementasi Merdeka Belajar Pendidikan Agama Islam di Tingkat Sekolah Dasar/Madrasah Ibtidaiyah Dengan Memanfaatkan Teknologi Informasi - Masruroh, Siti; Haerudin, Haerudin; Priyatna, Bayu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) IAIN Manado, 2023)
The purpose of study program-based community service is as an effort by lecturers to carry out the tridarma of higher education. In this case the Directorate General of Islamic Higher Religious Education (Diktis) provides a national level grant program for all lecturers under the ministry of religion. On this occasion, we propose a service with the theme Implementation of Freedom to Learn Islamic Religious Education at the Elementary School/Madrasah Ibtidaiyah Level by utilizing Information Technology, namely making an application